Structure and semantic complex of the story "Ardak" O. Bokeev (Eurasian Journal of Philology Science and Education, 2023)
In the article, using the model of the structural-semantic complex, the story of the famous writer Oralkhan Bokeev «Ardak» is analyzed.A complete and versatile analysis of a literary text is possible due to the allocation of various levels when modeling the structure of the text. The components of each level perform certain artistic functions. The model reveals the idea and theme of the work, examines the plot and composition, determines the structure of the narrative, highlights the chronotope of the work.In this article, these issues were solved by highlighting the ideological-thematic, plot-compositional, spatial-temporal, descriptive and speech levels. The division of a literary text into levels contributes to a more thorough and comprehensive analysis of a prose work, which helps to reveal its integrity.A small volume, a specific case from the life of the heroes of the story, the dynamism of the plot, the description of the characters and the landscape are aimed at a more capacious transfer of the idea of the work.The study of all levels of the literary text allowed to reveal new facets in the writer's work, to understand the originality of his worldview, worldview, to identify the peculiarities of mastery in depicting the phenomena of reality. In this regard, theoretical modeling is the most productive and effective way to comprehend the world of a literary work.Keywords: level, plot, composition, space, time, portrait, speech